2022
DOI: 10.53370/001c.34273
|View full text |Cite
|
Sign up to set email alerts
|

An improved Aquila optimization with fuzzy model based energy efficient cluster routing protocol for wireless sensor networks

Abstract: Due to the latest advances in microelectronics, wireless sensor networking (WSN) has been introduced in many applications. The flow of event data in WSN applications requires timely and reliable distribution so that immediate response and appropriate action can be taken. However, the limited power supply to the sensor terminal causes a transmission between the delay on the way to the base station and the power consumption. Clustering techniques are essential in developing the WSN routing algorithm that improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The improved versions of AO can handle a large range of difficult real-world optimization problems better than the standard AO. The strategies used in AO are hybridization with NIOAs [22,23], oppositional-based learning [24], chaotic sequence [25], Levy flight-based strategy [26], Gauss map and crisscross operator [27], Niche Thought with Dispersed Chaotic Swarm [28], random learning mechanism and Nelder-Mead Simplex Search [29], wavelet mutation [30], Weighted Adaptive Searching Technique [31], Binay AO [32], and multi-objective AO [33].…”
Section: Previous Work On Ao and Dolmentioning
confidence: 99%
“…The improved versions of AO can handle a large range of difficult real-world optimization problems better than the standard AO. The strategies used in AO are hybridization with NIOAs [22,23], oppositional-based learning [24], chaotic sequence [25], Levy flight-based strategy [26], Gauss map and crisscross operator [27], Niche Thought with Dispersed Chaotic Swarm [28], random learning mechanism and Nelder-Mead Simplex Search [29], wavelet mutation [30], Weighted Adaptive Searching Technique [31], Binay AO [32], and multi-objective AO [33].…”
Section: Previous Work On Ao and Dolmentioning
confidence: 99%
“…The study findings demonstrated that the presented techniques perform better than SA, GA, ACO, and GA-PSO. A cluster-based energy-efficient routing protocol for WSNs was proposed by Ramamoorthy et al [ 74 ], using an optimization technique. A modified AO with fuzzy based on the levy flight strategy was developed for optimum and effective cluster formation and cluster head computation.…”
Section: Related Work On Classical Ao and Its Improved Variantsmentioning
confidence: 99%